Global E-waste management: Can WEEE make a difference? A review of e-waste trends, legislation, contemporary issues and future challenges. (1st February 2021) - Shittu, Olanrewaju S.; Williams, Ian D.; Shaw, Peter J.
Highlights: Contemporary review of trends/insights to established/emerging e-waste issues. Four typical future WEEE management scenarios are identified & discussed. Emerging concerns: stockpiling; reuse standards; obsolescence; IoT, space e-debris. Key areas of concern & measures to improve WEEE management identified & recommended. Generation & management data standardisation required alongside political solutions. Abstract: Waste electrical and electronic equipment (WEEE) comprises a globally important waste stream due to the scarcity and value of the materials that it contains; annual generation of WEEE is increasing by 3–5% per annum. The effective management of WEEE will contribute critically to progress towards (1) realisation of the United Nations' Sustainable Development Goals, (2) a circular economy, and (3) resource efficiency. This comprehensive review paper provides a critical and contemporary examination of the current global situation of WEEE management and discusses opportunities for enhancement. Trends in WEEE generation, WEEE-related policies and legislation are exemplified in detail. Four typical future WEEE management scenarios are identified, classified and outlined. The European Community is at the forefront of WEEE management, largely due to the WEEE Directive (Directive 2012/19/EU) which sets high collection and recycling targets for Member States. WEEE generation rates are increasing in Africa though collection and recycling rates are low. WEEE-related legislation coverage is increasing in Asia (notably China and India) and in Latin America. This review highlights emerging concerns, including: stockpiling of WEEE devices; reuse standards; device obsolescence; the Internet of Things, the potential for collecting space e-debris, and emerging trends in electrical and electronic consumer goods. Key areas of concern in regard to WEEE management are identified: the partial provision of formal systems for WEEE collection and treatment at global scale; further escalation of global WEEE generation (increased ownership, and acceleration of obsolescence and redundancy); and absence of regulation and its enforcement. Measures to improve WEEE management at global scale are recommended: incorporation of circular economy principles in EEE design and production, and WEEE management, including urban mining; extension of WEEE legislation and regulation, and improved enforcement thereof; harmonisation of key terms and definitions to permit consistency and meaning in WEEE management; and improvements to regulation and recognition of the informal WEEE management sector.